DAYA DUKUNG, DAYA TAMPUNG SERTA AKSESIBILITAS VERTIKAL BANGUNAN KAMPUS SEBAGAI SHELTER TSUNAMI DI UNIVERSITAS NEGERI PADANG - jelly ana; Iswandi U (JURUSAN GEOGRAFI FIS UNP, 2020)
This research is motivated by the lack of knowledge of UNP students about tsunami shelter information in the UNP environment. The purpose of this study was to determine: 1) Carrying capacity 2) Capacity 3) Accessibility of campus buildings as tsunami shelters at UNP. This study uses a quantitative method with observations and measurements in 22 buildings that have a number of building floors of 3 and more than 3. The results of this study are the total population of UNP in 2019 is 33,828 people. Carrying capacity of 22 campus buildings, namely buildings that have a capacity of <1000 inhabitants, namely the New Postgraduate building, 1000-2000 inhabitants of SD UNP Building, Integrated C, Integrated B, MKU A, Central Library, your Rectorat Research Center, FPP Laboratory, and Mosque Al-Azhar, 2000-3000 people Integrated Building A, Postgraduate, Mining Engineering, Laboratory of the Faculty of Engineering and MKU B, 3000-4000 people are the Integrated Building of Economics, SMP UNP Development, Language and Art Laboratory, SMA UNP Development and Hospotality Center, and> 4000 inhabitants of the Education Faculty, Language and Arts and Psychology Faculty, FIP UNP. Vertical access (stairs) that is outside the building and easy to reach, namely in buildings, namely SMA, SMP and SD UNP Development, MKU A, MKU B, Central Library, Language and Art Laboratory, Mining Engineering, Postgraduate New and Integrated Economics.